A quick-dissolving anti-salt polyacrylamide thickening agent for fracturing and a preparation method thereof

CN122978352APending Publication Date: 2026-10-27DAQING VOLIGI TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611291798.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-25
Publication Date
2026-10-27

AI Technical Summary

Benefits of technology

[0018](1)、极速溶解,适配现场连续施工,产品可直接使用油田高矿化度盐水、返排液配液,常温完全溶解时间≤3min,无抱团、无结块,无需提前泡胶、无需长时间高速搅拌,完美适配油田连续混配压裂新工艺,大幅提升施工效率、降低设备能耗。

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present application belongs to the technical field of oilfield hydraulic fracturing, and particularly relates to a kind of quick-dissolving anti-salt polyacrylamide thickening agent for fracturing and a preparation method thereof. The thickening agent is prepared by copolymerization of 72.5 parts of acrylamide, 20 parts of dimethylaminoethyl acrylate, 8 parts of 2-acrylamido-2-methylpropanesulfonic acid, 6 parts of sodium allylsulfonate, 3 parts of N-vinylpyrrolidone, 2 parts of methyl acrylamide, 0.165 parts of a composite initiator, 0.93 parts of a fracturing special stabilizer, 3 parts of a pH regulator, and 135 parts of deionized water. The process is stable and green industrialization. The low-temperature aqueous solution copolymerization process is used without organic solvent and three-waste emissions. The reaction conditions are mild and the parameters are controllable. The product batch performance is stable. The technical problems of slow dissolution, fast viscosity attenuation in high-salt conditions, poor shear resistance, high gel-breaking residue, and large reservoir damage of traditional products are solved. The preparation process is simplified, the product batch stability is improved, and the oilfield continuous mixing and fracturing construction process is adapted.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of oilfield hydraulic fracturing technology, specifically relating to a fast-dissolving, salt-resistant polyacrylamide thickener for fracturing and its preparation method. Background Technology

[0002] Hydraulic fracturing is a core technology for enhancing the production and stimulation of tight oil, shale gas, and low-permeability oil and gas reservoirs. The fracturing fluid thickener is a key additive that determines the proppant-carrying, drag-reducing, and fracture-creating performance of the fracturing fluid. Currently, the mainstream fracturing thickeners in oilfields are mainly ordinary polyacrylamide, guar gum, and modified cellulose. Among them, polyacrylamide is the most widely used due to its low cost, good drag-reducing effect, and ease of preparation. However, existing conventional and modified polyacrylamide fracturing-specific products have significant technical shortcomings and cannot meet the fracturing construction needs of current high-salt, deep, and high-temperature oil and gas reservoirs.

[0003] Three major challenges exist in on-site construction: First, poor solubility. Conventional polyacrylamide powder readily clumps together when exposed to water, requiring soaking for over 30 minutes and high-speed mixing beforehand. This fails to meet the continuous mixing and rapid construction requirements of oilfields, severely impacting construction efficiency. Second, weak salt and shear resistance. Oilfields often use high-saltification formation water and fracturing flowback water for fluid preparation. High concentrations of calcium, magnesium, and sodium ions compress the double electric layer of polymer molecules, causing rapid molecular chain shrinkage and aggregation. High-speed shearing and temperature increases during fracturing further lead to a sharp decrease in viscosity, resulting in insufficient proppant carrying capacity, increased friction, and fracturing fluid failure. Third, significant reservoir damage. Traditional modified polyacrylamide is not completely broken down, resulting in high residue content, which easily clogs reservoir pores and fractures, significantly reducing oil and gas well productivity. Furthermore, its poor temperature stability leads to severe performance degradation at around 90℃, limiting its applicability to a wide range of reservoirs.

[0004] Currently, most patented and product-specific modified polyacrylamides for fracturing focus on optimizing either temperature resistance or salt tolerance, failing to achieve the comprehensive fracturing-specific performance characteristics of rapid dissolution, high salt resistance, shear resistance, low residue, and easy gel breaking. Furthermore, their manufacturing processes are complex, and batch stability is poor, making them unsuitable for continuous large-scale oilfield operations. Therefore, developing a dedicated fracturing polyacrylamide thickener that is suitable for high-salinity brine preparation, dissolves rapidly, is shear resistant, and minimizes reservoir damage is an urgent need in the oil and gas fracturing additive field. Summary of the Invention

[0005] The purpose of this invention is to overcome the shortcomings of the prior art and provide a composite oil phase dispersant for polyacrylamide granulation, its preparation method, and its application. This invention solves the technical problems of traditional products, such as slow dissolution, rapid viscosity decay under high-salt conditions, poor shear resistance, high residue after gel breaking, and significant reservoir damage. Simultaneously, it simplifies the preparation process, improves batch stability, and is suitable for continuous mixing and fracturing operations in oilfields.

[0006] The technical solution adopted in this invention is as follows: a fast-dissolving, salt-resistant polyacrylamide thickener for fracturing, the components and parts by weight of which are: 65-80 parts of acrylamide, 15-25 parts of dimethylaminoethyl acrylate, 6-10 parts of 2-acrylamido-2-methylpropanesulfonic acid, 4-8 parts of sodium allyl sulfonate, 2-4 parts of N-vinylpyrrolidone, 1-3 parts of methacrylamide, 0.08-0.25 parts of composite initiator, 0.6-1.8 parts of fracturing-specific stabilizer, 2-4 parts of pH adjuster, and 110-160 parts of deionized water.

[0007] The composite initiator is a low-temperature redox initiation system, composed of potassium persulfate and sodium bisulfite in a mass ratio of 2:1; the fracturing-specific stabilizer is composed of ethylene glycol, triethanolamine, and sodium thiosulfate in a mass ratio of 2:1:1, which has the functions of salt resistance, heat resistance, and degradation inhibition; the pH adjuster is sodium carbonate or sodium bicarbonate.

[0008] Furthermore, the components and weight parts of the fast-dissolving, salt-resistant polyacrylamide thickener for fracturing are as follows: 65 parts acrylamide, 15 parts dimethylaminoethyl acrylate, 6 parts 2-acrylamido-2-methylpropanesulfonic acid, 4 parts sodium allyl sulfonate, 2 parts N-vinylpyrrolidone, 1 part methacrylamide, 0.08 parts composite initiator, 0.6 parts fracturing-specific stabilizer, 2 parts pH adjuster, and 110 parts deionized water.

[0009] Furthermore, the components and weight parts of the fast-dissolving, salt-resistant polyacrylamide thickener for fracturing are as follows: 72.5 parts acrylamide, 20 parts dimethylaminoethyl acrylate, 8 parts 2-acrylamido-2-methylpropanesulfonic acid, 6 parts sodium allyl sulfonate, 3 parts N-vinylpyrrolidone, 2 parts methacrylamide, 0.165 parts composite initiator, 0.93 parts fracturing-specific stabilizer, 3 parts pH adjuster, and 135 parts deionized water.

[0010] Furthermore, the components and weight parts of the fast-dissolving, salt-resistant polyacrylamide thickener for fracturing are as follows: 80 parts acrylamide, 25 parts dimethylaminoethyl acrylate, 10 parts 2-acrylamido-2-methylpropanesulfonic acid, 8 parts sodium allyl sulfonate, 4 parts N-vinylpyrrolidone, 3 parts methacrylamide, 0.25 parts composite initiator, 1.8 parts fracturing-specific stabilizer, 4 parts pH adjuster, and 160 parts deionized water.

[0011] A method for preparing a fast-dissolving, salt-resistant polyacrylamide thickener for fracturing includes the following steps:

[0012] Step 1: Add 110-160 parts of deionized water to a closed polymerization reactor. Under the condition of uniform stirring at room temperature (25-30℃), add 65-80 parts of acrylamide, 15-25 parts of dimethylaminoethyl acrylate, 6-10 parts of 2-acrylamido-2-methylpropanesulfonic acid, 4-8 parts of sodium allyl sulfonate, 2-4 parts of N-vinylpyrrolidone, and 1-3 parts of methacrylamide monomer to the reactor in sequence. Continue stirring for 15-25 minutes until all monomers are completely dissolved, forming a clear and homogeneous monomer aqueous solution.

[0013] Step 2: Continuously purge high-purity nitrogen gas into the monomer aqueous solution from Step 1 for 20-35 minutes, then add pH adjuster in batches to adjust the pH value of the system to 6.8-7.3.

[0014] Step 3: Adjust the temperature of the system from Step 2 to 38-42℃, add the composite initiator at a uniform rate, and control the addition time to 30-40 minutes. After the addition is completed, seal and maintain the temperature for polymerization for 3.5-4.5 hours to generate polymer colloid.

[0015] Step 4: After the polymerization in Step 3 is completed, heat the reactor to 82-88℃, add the fracturing stabilizer, and keep it at a constant temperature for 2-3 hours for modification.

[0016] Step 5: Take out the modified polymer colloid from Step 4, and perform mechanical granulation, low-temperature hot air drying and pulverization and sieving. Control the powder mesh size to 200 mesh and the drying temperature to 55-65℃ to finally obtain the finished product of fast-dissolving salt-resistant polyacrylamide thickener for fracturing.

[0017] The beneficial effects of this invention: This invention provides a fast-dissolving, salt-resistant polyacrylamide thickener for fracturing and its preparation method, the main advantages of which are as follows:

[0018] (1) Rapid dissolution, suitable for continuous on-site construction. The product can be directly used to prepare high-mineralized brine and flowback fluid from oilfields. The complete dissolution time at room temperature is ≤3min. There is no clumping or agglomeration. No need to soak the glue in advance or stir at high speed for a long time. It is perfectly adapted to the new continuous mixing and fracturing process in oilfields, which greatly improves construction efficiency and reduces equipment energy consumption.

[0019] (2) It has strong salt and shear resistance and wide adaptability to working conditions. It can be adapted to high salt systems with mineralization of 0-35000mg / L. Under high temperature and high speed shear conditions of 90℃, the viscosity retention rate is ≥92%. The sand carrying performance is stable throughout the fracturing process and the drag reduction effect is excellent. The drag reduction rate is ≥72%, which can effectively reduce the friction of the tubing and improve the fracturing and fracture creation effect.

[0020] (3) Low residue and low damage, good reservoir protection, controllable molecular structure and no difficult-to-degrade cross-linked structure. It can completely break the gel after fracturing. The residue content of the breaking liquid is ≤28mg / L, which is far below the industry standard. It will not block the reservoir pores and fractures, protect the oil and gas reservoir to the greatest extent, and ensure the long-term production capacity of oil and gas wells.

[0021] (4) The process is stable and green industrialization is achieved by using a low-temperature aqueous solution copolymerization process. There are no organic solvents or waste emissions. The reaction conditions are mild and the parameters are controllable. The product batches have stable performance and can be mass-produced on a large scale. The production cost is lower than that of imported salt-resistant fracturing thickeners, and the cost-performance advantage is significant.

[0022] (5) It is versatile and adaptable to various scenarios. It can be used as a thickener for fracturing fluid to enhance the sand-carrying and fracturing capacity, or as a drag-reducing agent for fracturing tubing. It is suitable for various field processes such as water fracturing, brine fracturing, and flowback fluid reuse fracturing. Detailed Implementation

[0023] Example 1

[0024] The preparation method of the fast-dissolving, salt-resistant polyacrylamide thickener for fracturing includes the following steps:

[0025] Step 1: Add 110 parts of deionized water to a closed polymerization reactor. Under constant temperature and speed stirring, add 65 parts of acrylamide, 15 parts of dimethylaminoethyl acrylate, 6 parts of 2-acrylamido-2-methylpropanesulfonic acid, 4 parts of sodium allyl sulfonate, 2 parts of N-vinylpyrrolidone, and 1 part of methacrylamide monomer to the reactor in sequence. Stir at a constant speed for 20 minutes until all monomers are completely dissolved to obtain a homogeneous transparent monomer aqueous solution.

[0026] Step 2: Continuously purge high-purity nitrogen gas into the monomer aqueous solution from Step 1 for 30 minutes, then add 2 parts of sodium carbonate in batches to adjust the pH of the system to 7.3.

[0027] Step 3: Adjust the temperature of the system from Step 2 to 40℃, and slowly and uniformly add 0.08 parts of the composite initiator. The addition time is 35 minutes. After the addition is completed, seal and maintain the temperature for 4 hours to obtain a highly elastic polymer colloid.

[0028] Step 4: After the polymerization in Step 3 is completed, heat the reactor to 85°C, add 0.6 parts of fracturing-specific stabilizer, and keep it at a constant temperature for 2.5 hours for modification.

[0029] Step 5: Take out the modified polymer colloid from Step 4, and perform mechanical granulation, low-temperature hot air drying and pulverization and sieving. Control the powder mesh size to 200 mesh and the drying temperature to 55-65℃ to finally obtain the finished product of fast-dissolving salt-resistant polyacrylamide thickener for fracturing.

[0030] Example 2

[0031] The preparation method of the fast-dissolving, salt-resistant polyacrylamide thickener for fracturing includes the following steps:

[0032] Step 1: Add 135 parts of deionized water to a closed polymerization reactor. Under constant temperature and speed stirring, add 72.5 parts of acrylamide, 20 parts of dimethylaminoethyl acrylate, 8 parts of 2-acrylamido-2-methylpropanesulfonic acid, 6 parts of sodium allyl sulfonate, 3 parts of N-vinylpyrrolidone, and 2 parts of methacrylamide monomer to the reactor in sequence. Stir at a constant speed for 20 minutes until all monomers are completely dissolved to obtain a homogeneous transparent monomer aqueous solution.

[0033] Step 2: Continuously purge high-purity nitrogen gas into the monomer aqueous solution from Step 1 for 30 minutes, then add 3 parts of sodium bicarbonate in batches to adjust the pH of the system to 7.3.

[0034] Step 3: Adjust the temperature of the system from Step 2 to 40℃, and slowly and uniformly add 0.165 parts of the composite initiator. The addition time is 35 minutes. After the addition is completed, seal and maintain the temperature for 4 hours to obtain a highly elastic polymer colloid.

[0035] Step 4: After the polymerization in Step 3 is completed, heat the reactor to 85°C, add 1.2 parts of fracturing-specific stabilizer, and keep it at a constant temperature for 2.5 hours for modification.

[0036] Step 5: Take out the modified polymer colloid from Step 4, and perform mechanical granulation, low-temperature hot air drying and pulverization and sieving. Control the powder mesh size to 200 mesh and the drying temperature to 55-65℃ to finally obtain the finished product of fast-dissolving salt-resistant polyacrylamide thickener for fracturing.

[0037] Example 3

[0038] The preparation method of the fast-dissolving, salt-resistant polyacrylamide thickener for fracturing includes the following steps:

[0039] Step 1: Add 160 parts of deionized water to a closed polymerization reactor. Under constant temperature and speed stirring, add 80 parts of acrylamide, 25 parts of dimethylaminoethyl acrylate, 10 parts of 2-acrylamido-2-methylpropanesulfonic acid, 8 parts of sodium allyl sulfonate, 4 parts of N-vinylpyrrolidone, and 3 parts of methacrylamide monomer to the reactor in sequence. Stir at a constant speed for 20 minutes until all monomers are completely dissolved to obtain a homogeneous transparent monomer aqueous solution.

[0040] Step 2: Continuously purge high-purity nitrogen gas into the monomer aqueous solution from Step 1 for 30 minutes, then add 4 parts of sodium carbonate in batches to adjust the pH of the system to 7.3.

[0041] Step 3: Adjust the temperature of the system from Step 2 to 40℃, and slowly and uniformly add 0.25 parts of the composite initiator. The addition time is 35 minutes. After the addition is completed, seal and maintain the temperature for 4 hours to obtain a highly elastic polymer colloid.

[0042] Step 4: After the polymerization in Step 3 is completed, heat the reactor to 85°C, add 1.6 parts of fracturing-specific stabilizer, and keep it at a constant temperature for 2.5 hours for modification.

[0043] Step 5: Take out the modified polymer colloid from Step 4, and perform mechanical granulation, low-temperature hot air drying and pulverization and sieving. Control the powder mesh size to 200 mesh and the drying temperature to 55-65℃ to finally obtain the finished product of fast-dissolving salt-resistant polyacrylamide thickener for fracturing.

[0044] Example 4 (Comparative Example)

[0045] We selected commercially available salt-resistant polyacrylamide fracturing thickener commonly used in oilfields and ordinary modified polyacrylamide for fracturing, and conducted parallel comparative experiments under the same test conditions.

[0046] Performance testing experiment

[0047] The test was conducted according to the "SY / T 5107-2016 Performance Evaluation Method for Water-Based Fracturing Fluids". The test conditions were: ambient temperature 25℃, water salinity of the prepared solution 35000 mg / L, test temperature 90℃, and shear rate 170 s. -1 The core performance indicators are as follows:

[0048] 1. The fast-dissolving, salt-resistant polyacrylamide thickener prepared in Example 1: the salt water dissolution time is 2.7 min, the viscosity retention rate is 92.1% after shearing at 90℃ for 2 h, the drag reduction rate of fracturing fluid is 72.3%, and the content of broken gel residue is 27.8 mg / L.

[0049] 2. The fast-dissolving, salt-resistant polyacrylamide thickener prepared in Example 2 (best example): salt water dissolution time 2.2 min, viscosity retention rate 96.5% after shearing at 90℃ for 2 h, drag reduction rate of fracturing fluid 75.2%, and gel breaking residue content 25.3 mg / L.

[0050] 3. The fast-dissolving, salt-resistant polyacrylamide thickener prepared in Example 3: the salt water dissolution time is 2.5 min, the viscosity retention rate is 93.7% after shearing at 90℃ for 2 h, the drag reduction rate of fracturing fluid is 73.6%, and the content of broken gel residue is 26.5 mg / L.

[0051] 4. Comparative product (commercially available modified polyacrylamide for fracturing): brine dissolution time 28.5 min, viscosity retention rate at 90℃ for 2 h, drag reduction rate of fracturing fluid 63.5%, and residue content after gel breaking 89.6 mg / L.

[0052] Test results show that the fracturing-specific polyacrylamide thickeners prepared in Examples 1-3 have a dissolution rate that is more than 10 times faster than existing ordinary modified polyacrylamides for fracturing, significantly improved high-temperature and high-salt shear resistance, better drag reduction effect, and significantly reduced residue content. They are perfectly suited to the fracturing construction needs of high-salt reservoirs, and their overall performance far exceeds that of existing commercial products.

Claims

1. A fast-dissolving, salt-resistant polyacrylamide thickener for fracturing, characterized in that: The components and weight parts of the fast-dissolving, salt-resistant polyacrylamide thickener for fracturing are as follows: 65-80 parts acrylamide, 15-25 parts dimethylaminoethyl acrylate, 6-10 parts 2-acrylamido-2-methylpropanesulfonic acid, 4-8 parts sodium allyl sulfonate, 2-4 parts N-vinylpyrrolidone, 1-3 parts methacrylamide, 0.08-0.25 parts composite initiator, 0.6-1.8 parts fracturing-specific stabilizer, 2-4 parts pH adjuster, and 110-160 parts deionized water; The composite initiator is a low-temperature redox initiation system, which is composed of potassium persulfate and sodium bisulfite in a mass ratio of 2:

1. The fracturing stabilizer is a mixture of ethylene glycol, triethanolamine and sodium thiosulfate in a mass ratio of 2:1:

1. The pH adjuster is sodium carbonate or sodium bicarbonate.

2. The fast-dissolving, salt-resistant polyacrylamide thickener for fracturing according to claim 1, characterized in that: The components and weight parts of the fast-dissolving, salt-resistant polyacrylamide thickener for fracturing are as follows: 65 parts acrylamide, 15 parts dimethylaminoethyl acrylate, 6 parts 2-acrylamido-2-methylpropanesulfonic acid, 4 parts sodium allyl sulfonate, 2 parts N-vinylpyrrolidone, 1 part methacrylamide, 0.08 parts composite initiator, 0.6 parts fracturing-specific stabilizer, 2 parts pH adjuster, and 110 parts deionized water.

3. The fast-dissolving, salt-resistant polyacrylamide thickener for fracturing according to claim 1, characterized in that: The components and weight parts of the fast-dissolving, salt-resistant polyacrylamide thickener for fracturing are as follows: 72.5 parts acrylamide, 20 parts dimethylaminoethyl acrylate, 8 parts 2-acrylamido-2-methylpropanesulfonic acid, 6 parts sodium allyl sulfonate, 3 parts N-vinylpyrrolidone, 2 parts methacrylamide, 0.165 parts composite initiator, 0.93 parts fracturing-specific stabilizer, 3 parts pH adjuster, and 135 parts deionized water.

4. The fast-dissolving, salt-resistant polyacrylamide thickener for fracturing according to claim 1, characterized in that: The components and weight parts of the fast-dissolving, salt-resistant polyacrylamide thickener for fracturing are as follows: 80 parts acrylamide, 25 parts dimethylaminoethyl acrylate, 10 parts 2-acrylamido-2-methylpropanesulfonic acid, 8 parts sodium allyl sulfonate, 4 parts N-vinylpyrrolidone, 3 parts methacrylamide, 0.25 parts composite initiator, 1.8 parts fracturing-specific stabilizer, 4 parts pH adjuster, and 160 parts deionized water.

5. A method for preparing a fast-dissolving, salt-resistant polyacrylamide thickener for fracturing, characterized in that: The preparation method of the thickener includes the following steps: Step 1: Add 110-160 parts of deionized water to a closed polymerization reactor. Under the condition of uniform stirring at room temperature (25-30℃), add 65-80 parts of acrylamide, 15-25 parts of dimethylaminoethyl acrylate, 6-10 parts of 2-acrylamido-2-methylpropanesulfonic acid, 4-8 parts of sodium allyl sulfonate, 2-4 parts of N-vinylpyrrolidone, and 1-3 parts of methacrylamide monomer to the reactor in sequence. Continue stirring for 15-25 minutes until all monomers are completely dissolved to obtain a homogeneous transparent monomer aqueous solution. Step 2: Continuously purge high-purity nitrogen gas into the monomer aqueous solution from Step 1 for 20-35 minutes, then add pH adjuster in batches to adjust the pH of the system to 6.8-7.3; Step 3: Adjust the temperature of the system from Step 2 to 38-42℃, add the composite initiator dropwise at a uniform rate, and control the dropwise addition time to 30-40 minutes. After the dropwise addition is completed, seal and maintain the temperature for 3.5-4.5 hours to generate a polymer colloid. Step 4: After the polymerization in Step 3 is completed, heat the reactor to 82-88℃, add the fracturing stabilizer, and keep it at a constant temperature for 2-3 hours for modification. Step 5: Take out the modified polymer colloid from Step 4, and perform mechanical granulation, low-temperature hot air drying and pulverization and sieving. Control the powder mesh size to 200 mesh and the drying temperature to 55-65℃ to finally obtain the finished product of fast-dissolving salt-resistant polyacrylamide thickener for fracturing.